Collaboration of business and science: a starting position for Lithuania’s move to radical economic change - Samulevičius, Jurgis (Business: Theory and Practice, 2012)
The concept of interaction between systems of research, teaching and practical businesses in the context of knowledge- based economy and management are presented in the article. The article shows how the general trends of the global knowledge- based economy can be adapted to conditions of Lithuania. Special attempt is made for analysis of bridging local business and academic problems, solutions of which are relevant to Lithuania in the context of knowledge and globalization. In this context special attempt is made for developing new business strategies which play roles of key drivers in moving Lithuania’s economy towards radical knowledge-based economic changes. The paper attempts to make proposals for generating and effective use of synergy effects through establishing science & technology parks, business incubators, transport hubs and innovation research centers near universities which sponsor and help to spread an innovative culture amongst businesses in Lithuania. Special attempt is made to accent academic and business collaboration as priority and starting position in the process of the creation of knowledge-based economy in Lithuania.